Frontotemporal Lobar Degeneration and MicroRNAs - Piscopo, Paola; Albani, Diego; Castellano, Anna E.; Forloni, Gianluigi; Confaloni, Annamaria (Frontiers in Aging Neuroscience, 2016)
Frontotemporal lobar degeneration (FTLD) includes a spectrum of disorders characterized by changes of personality and social behavior and, often, a gradual and progressive language dysfunction. In the last years, several efforts have been fulfilled in identifying both genetic mutations and pathological proteins associated with FTLD. The molecular bases undergoing the onset and progression of the disease remain still unknown. Recent literature prompts an involvement of RNA metabolism in FTLD, particularly microRNAs (miRNAs). Dysregulation of miRNAs in several disorders, including neurodegenerative diseases, and increasing importance of circulating miRNAs in different pathologies has suggested to implement the study of their possible application as biological markers and new therapeutic targets; moreover, miRNA-based therapy is becoming a powerful tool to deepen the function of a gene, the mechanism of a disease, and validate therapeutic targets. Regarding FTLD, different studies showed that miRNAs are playing an important role. For example, several reports have evaluated miRNA regulation of the progranulin gene suggesting that it is under their control, as described for miR-29b, miR-107, and miR-659. More recently, it has been demonstrated that TMEM106B gene, which protein is elevated in FTLD-TDP brains, is repressed by miR-132/212 cluster; this post-transcriptional mechanism increases intracellular levels of progranulin, affecting its pathways. These findings if confirmed could suggest that these microRNAs have a role as potential targets for some related-FTLD genes. In this review, we focus on the emerging roles of the miRNAs in the pathogenesis of FTLD.